Advances in research on the role of high carbohydrate diet in the process of inflammatory bowel disease (IBD) - Zhang, Ying; Xun, Linting; Qiao, Ran; Jin, Shumei; Zhang, Bing; Luo, Mei; Wan, Ping (Frontiers in Immunology, 2024)
Inflammatory bowel disease (IBD) is a chronic, systemic gastrointestinal disorder characterized by episodic inflammation that requires life-long management. Although the etiology of IBD is not fully understood, it is hypothesized to involve a multifaceted interplay among genetic susceptibility, the host immune response, and environmental factors. Previous studies have largely concluded that IBD is associated with this complex interplay; however, more recent evidence underscores the significant role of dietary habits as risk factors for the development of IBD. In this review, we review the molecular mechanisms of high-sugar and high-fat diets in the progression of IBD and specifically address the impacts of these diets on the gut microbiome, immune system regulation, and integrity of the intestinal barrier, thereby highlighting their roles in the pathogenesis and exacerbation of IBD.